Please, What is the answer?

Explanation:
You can verify this by plugging each root into the equation.
So for instance, plug in x = -2 and we get
f(x) = -3*(x+2)*(x-sqrt(3))*(x-4)
f(-2) = -3*(-2+2)*(-2-sqrt(3))*(-2-4)
f(-2) = -3*(0)*(-2-sqrt(3))*(-2-4)
f(-2) = 0
This verifies x = -2 is a root.
All that matters is that zero buried in there in the second to last step. Multiplying 0 by anything leads to 0. The other roots are verified in the same manner. The -3 out front is the leading coefficient.
----------------
Extra info: